2017
DOI: 10.1016/j.jpsychores.2017.07.015
|View full text |Cite
|
Sign up to set email alerts
|

Increased incidence of psychiatric disorders in immune-mediated inflammatory disease

Abstract: Individuals with IMID, including IBD, MS and RA are at increased risk of psychiatric comorbidity. This increased risk appears non-specific as it is seen for all three IMIDs and for all psychiatric disorders studied, implying a common underlying biology for psychiatric comorbidity in those with IMID.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
85
0
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 148 publications
(95 citation statements)
references
References 51 publications
8
85
0
2
Order By: Relevance
“…These findings are consistent with available epidemiological evidence indicating that the presence of one set of disorders portends increased risk for a diagnosis from the other class of disorders, though the causality and temporality of these relationships is not clearly established. [76][77][78][79][80][81][82] Positive genetic inter-correlations among these phenotypes are also consistent with recent work demonstrating that the positive correlation between BD and SZ are significantly mediated by both CNS and immunologic tissues. 83 Our local genetic correlation analyses were inadequately powered to detect loci relevant to most of the psychiatric-immune disorder pairs, including BD.…”
Section: Discussionsupporting
confidence: 89%
“…These findings are consistent with available epidemiological evidence indicating that the presence of one set of disorders portends increased risk for a diagnosis from the other class of disorders, though the causality and temporality of these relationships is not clearly established. [76][77][78][79][80][81][82] Positive genetic inter-correlations among these phenotypes are also consistent with recent work demonstrating that the positive correlation between BD and SZ are significantly mediated by both CNS and immunologic tissues. 83 Our local genetic correlation analyses were inadequately powered to detect loci relevant to most of the psychiatric-immune disorder pairs, including BD.…”
Section: Discussionsupporting
confidence: 89%
“…We identified 10,206 individuals with incident RA, and 50,960 matched controls. Nearly three‐quarters were women, with a mean ± SD age at the index date of 53.7 ± 16.0 years (Table ) .…”
Section: Resultsmentioning
confidence: 99%
“…As described elsewhere , we applied validated case definitions for identifying depression, anxiety disorder, bipolar disorder, and schizophrenia (see , available on the Arthritis Care & Research web site at http://onlinelibrary.wiley.com/doi/10.1002/acr.23539/abstract) to identify affected individuals . To estimate the incidence of these psychiatric disorders after RA diagnosis (or the index date in matched controls), the first claim for the psychiatric disorder had to occur after the index date, and had to be preceded by a 5‐year period with no claims for that psychiatric disorder.…”
Section: Methodsmentioning
confidence: 99%
“…Chronic disorders, such as CD not only affect physical health, but also mental health, thereby increasing the chances of acquiring comorbid mood disorders including depression or anxiety (5)(6)(7). In fact, it has also been shown that persons with CD are more likely to have depression or anxiety antedating CD diagnosis by years, suggesting possible shared risk factors for both chronic mental health disorders and CD (8,9). Physiologically, as a threat to homeostasis, there are a number of mechanisms by which stress may impact the gastrointestinal tract (10).…”
Section: Introductionmentioning
confidence: 99%